PERLINDUNGAN KONSUMEN BANK TERHADAP TIDAK TANGGUNG JAWABNYA BANK DALAM KASUS PENIPUAN KODE ONE TIME PASSWORD DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Putusan Nomor 170 K/Pdt. Sus-BPSK/2020) - Regina Christhalia; Jeane Neltje Sally (Jurnal Hukum Adigama, 2022)
The purpose of writing this journal or article is to find out how Bank Consumer Protection Against Bank Actions in OTP Code Fraud Cases is viewed from Law Number 8 of 1999 concerning Consumer Protection. By using the library study research method based on laws and regulations, it can be concluded that bank customers as consumers need to be protected in accordance with legal provisions, and banks also need to apply the precautionary principle and be responsible for consumers in accordance with existing regulations. But sometimes there are problems between the customer and the bank. One of them is the problem with decision No. 170 K/Pdt. Sus-BPSK/2020 . From the writing that was done, it can be seen that the decision of the lawsuit in Article 19 paragraphs 1 and 3 of the Consumer Protection Act states that consumers who feel aggrieved can directly claim compensation from the producer and must provide a response and or be resolved within 7 days after the transaction takes place.